Pengaruh Penambahan Partikel Nikel Terhadap Swat Fisis Dan Mekanis Alumina Yang Mengandung 20% Berat Silika - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Ceramics are materials which generally have excellent properties such as high melting point, high hardness, good wear resistance, good corrosion resistance, relatively low density, and low thermal expansion. Ceramics, however, have limitation in engineering applications because of their brittleness and low fracture toughness. The present study aims to investigate the effect of nickel particles addition on physical and mechanical properties of alumina. Alumina (containing 20% weight SiO2) as matrix was reinforced with (0, 3, 6, 9, 12, and 15% volume) nickel. Three green samples with different dimensions i.e. cylindrical (15 mm diameter), square (50x7x8 mm3) and square (50x7x8 mm3) with a V-notch prepared using uni-axial steel die with a pressure of 120 MPa. The cylindrical samples were pressureless sintered at various temperatures of 1400Â°C, 14250C and 14500C and a holding time of 60 minutes. Sintering at 1425Â°C was found to be the optimum temperature to get the highest density of samples and this temperature was chosen to produce samples for mechanical testing. Hardness of these samples was measured using Vickers hardness test with a load of 153.2 N and the results showed that the Vickers hardness decreased from 824 MPa (0% volume nickel) to 540 MPa (15% volume nickel). Single-Edge Notched Beam method was used to determine the fracture toughness measurement and the results showed that the fracture toughness increased from 0.76 MPa.m1/2 (0% volume nickel) to 1.03 MPa.ml/2 (12% volume nickel). The increase of fracture toughness was due to crack deflection, crack bridging and crack branching mechanisms. The strength of the samples was measured using four point bending test. The bending strength increased with increasing nickel content up to 12% volume. Optical microscopy and SEM were used to observe the microstructures and fracture surface of samples.